1998
DOI: 10.1080/07315724.1998.10718751
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Supplementation and Exercise Performance: An Update

Abstract: Creatine, a natural nutrient found in animal foods, is alleged to be an effective nutritional ergogenic aid to enhance sport or exercise performance. Research suggests that oral creatine monohydrate supplementation may increase total muscle creatine [TCr], including both free creatine [FCr] and phosphocreatine [PCr]. Some, but not all, studies suggest that creatine supplementation may enhance performance in high-intensity, short-term exercise tasks that are dependent primarily on PCr (i.e., < 30 seconds), part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
2
17

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(100 citation statements)
references
References 35 publications
0
78
2
17
Order By: Relevance
“…
Creatine (Cr) is an endogenous as well as an exogenous compound related with high-energy metabolism [1,2]. During muscular exercise, ATP is directly used for mechanical contractions of actin and myosin filaments.
…”
mentioning
confidence: 99%
“…
Creatine (Cr) is an endogenous as well as an exogenous compound related with high-energy metabolism [1,2]. During muscular exercise, ATP is directly used for mechanical contractions of actin and myosin filaments.
…”
mentioning
confidence: 99%
“…Although the creatine kinase system is not the principal energy supplier during an 800 m wheelchair race, an increased level of phosphocreatine may possibly diminish lactic acid formation 20 and therefore enhance performance. This provides some evidence for the use of creatine supplementation for exercise bouts lasting longer than 30 s. In fact, a significant increase of 8.5% of time to exhaustion from 130 to 141 s at a workload corresponding to 125% of maximal oxygen uptake during cycle ergometry was demonstrated, 6 and Prevost et al 8 found a 23.5% increase of total work time during cycling at 150% peak oxygen uptake.…”
Section: Discussionmentioning
confidence: 99%
“…For at least 50 years, creatine is already well known to scientists and professional athletes (1). However, creatine supplementation with athletic intent began to gain popularity in the 1992 Olympics in Barcelona, when British sprinter Linford Christie won the 100-m dash and linked his gold medal to creatine intake (2).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, creatine monohydrate supplementation aims to saturate the remaining 20 to 40% (5). Oral creatine monohydrate supplementation could increase the total amount of muscle creatine, which in turn could also increase free creatine and phosphocreatine (PCr) (1,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation